DINAMIKA MERGER SEKOLAH: ANTARA PENGEMBANGAN DAN PROBLEM SEKOLAH - Wahdan Najib Habiby; Aninda Tetrasari ZH; Rofiqoh Maldinni; Ita Noer Pratiwi; Fitri Nur Wulandari; Qorin Umdatul Millah (Universitas Muhammadiyah Surakarta, 2018)
The purpose of this study is expected to provide an understanding of the effects of school mergers carried out by SD Sondakan No. 11 Surakarta. In addition, the results of this study can be useful for educational institutions, especially for schools that experience impacts. The merger policy of schools in Surakarta Sondakan State Elementary School No.11 has a positive impact on learning activities in schools, the realization of a comfortable and conducive learning environment. the implementation of activities to develop students' talents through extracurricular activities. The existence of literacy activities before implementing learning. Able to follow and win champions from various competitions both academic and non-academic. For example CCAI competition, PHBS, persami, etc. Negative influence after the school merger for students, social influence, especially in the economic strata. Because guardians of students from these 3 elementary schools have different economies. So that there are still some students who feel isolated and lacking in confidence.